Consociationalism and Power-Sharing in Europe
XIX, 209 p. 3 illus.
Keywords: This book examines the theoretical and practical relevance and challenges of the consociationalist model of democracy. Since the publication of the Politics of Accommodation (1968) and Democracy in Plural Societies (1977) Professor Lijphart’s theories and practical implementations have played a key role in establishing enduring peace settlements. In this edited volume, scholars and Professor Lijphart himself critically examine the history of consocationalism and its application in areas including Northern Ireland, Bosnia-Herzegovina, and Colombia. The book will be essential reading for undergraduate and graduate students of political science, comparative politics, transitional justice and peace studies. It will also be of use to practitioners ranging from diplomats to NGOs who are interested in the practical application of tested models of political accommodation.